Clinical Practice Guidelines for Bladder Cancer 2019 edition by the Japanese Urological Association: Revision working position paper. (14th March 2020) - Matsumoto, Hiroaki; Shiraishi, Koji; Azuma, Haruhito; Inoue, Keiji; Uemura, Hirotsugu; Eto, Masatoshi; Ohyama, Chikara; Ogawa, Osamu; Kikuchi, Eiji; Kitamura, Hiroshi; Shinohara, Nobuo; Takahashi, Satoru; et al.
Abstract: The Clinical Practice Guidelines for Bladder Cancer edited by the Japanese Urological Association were first published in 2009 and a revised edition was released in 2015. Four years has passed since the 2015 edition, and the clinical practice environment surrounding bladder cancer has drastically changed during that time. The main changes include: (i) insurance coverage of a new diagnostic method for non‐muscle‐invasive bladder cancer; (ii) insurance coverage of an immune checkpoint inhibitor in advanced and metastatic bladder cancer; and (iii) advances in robot‐assisted radical cystectomy as a minimally invasive treatment for muscle‐invasive bladder cancer. A paradigm shift in bladder cancer diagnosis and treatment is occurring day by day. Therefore, in this 2019 edition, while dealing with the above changes, we carefully selected clinical questions with clear evidence and included other clinically important points in the general statement. We also added a new chapter on rare cancers of the urinary tract. As a new method for the evaluation of study evidence level, we introduce "The Grading of Recommendations Assessment, Development and Evaluation" system modified to Japanese by the Medical Information Network Distribution Service.